Analisis Model Pencapaian Konsep Akhlak pada Buku PAI dan Budi Pekerti Kelas VII - Ghiyats, Achmad Ghiyats Setiawan; Syahidin, Syahidin (EduInovasi: Journal of Basic Educational Studies, 2025)
According to Piaget (1972) and Kohlberg (1981), adolescents' moral development is at the conventional stage, where they tend to follow moral values taught by authority or society. Therefore, effective learning strategies in achieving moral concepts in students in this age range must be relevant to their stage of moral development. Research by (Hasanah, 2018 Rahmawati & Santoso, 2019) shows that the application of appropriate learning models, such as moral reflection methods and value discussions, can improve students' understanding and appreciation of moral concepts.The research method used in this study is a qualitative approach with a library research method or literature study. This approach aims to understand the phenomenon in depth through the analysis of various literatures, such as books, scientific journals, articles, and other relevant documents. there are several approaches in the moral achievement model, namely the theoretical approach, practical approach, and reflective approach. With the application of this achievement model, it is expected that students can understand and absorb the moral values taught, apply religious teachings in their daily lives, and can become individuals who have good character, faith, and responsibility. Therefore, it is very important for educators to combine these three approaches in the learning process of Islamic Religious Education in order to create an effective and meaningful learning environment.